1988
DOI: 10.1002/cm.970090310
|View full text |Cite
|
Sign up to set email alerts
|

Cell model contraction in the ciliate spirostomum

Abstract: As the species name indicates, the large heterotrichous ciliate Spirostomum umbiguum is characterized by a twisting contraction of the cell body that is easily triggered by various kinds of external stimuli. On the basis of morphological studies, contraction and extension of this organism have been considered to result from antagonistic actions of myoneme and microtubular ribbons. After many trials, we have succeeded in preparing cell models to examine induced contractions and extensions of the cell body. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A large number of investigations have been made on the Ca 2ϩ -dependent contraction of the glycerinated stalk of vorticellid ciliates [Asai et al, 1978;Ochiai et al, 1979;Yokoyama and Asai, 1987] and Triton-extracted models of heterotrichous ciliates [Ishida and Shigenaka, 1988;Ishida et al, 1996]. They showed that such contractions occur in an all-or-none fashion [Katoh and Kikuyama, 1997;Moriyama et al, 1998].…”
Section: Discussionmentioning
confidence: 98%
“…A large number of investigations have been made on the Ca 2ϩ -dependent contraction of the glycerinated stalk of vorticellid ciliates [Asai et al, 1978;Ochiai et al, 1979;Yokoyama and Asai, 1987] and Triton-extracted models of heterotrichous ciliates [Ishida and Shigenaka, 1988;Ishida et al, 1996]. They showed that such contractions occur in an all-or-none fashion [Katoh and Kikuyama, 1997;Moriyama et al, 1998].…”
Section: Discussionmentioning
confidence: 98%
“…Gruberia is quite similar to Spirostomum, but they differ in relation to the mode of contraction and paroral infraciliature. Body contraction in Spirostomum is helical because of the presence of microtubular fibers forming a counterclockwise spiral from the anterior to the posterior end (Ishida and Shigenaka, 1988). In Gruberia, the contraction is longitudinal, i.e., along the antero-posterior axis of the body (Dragesco and Dragesco-Kernéis, 1986).…”
Section: Phylogenetic Position Of Gruberiamentioning
confidence: 98%
“…Many authors state in their descriptions that Spirostomum species lack a paroral membrane (TUFFRAU 1967, REPAK & ISQUITH 1974, ISHIDA et al 1988. However, FERNANDEZ-LEBORANS (1985) …”
Section: Molecular Characterizationmentioning
confidence: 99%
“…The name Spirostomum refers to the ability these ciliates have to contract in a spiral mode. This type of contraction is due to the presence of post-ciliary, sub-pellicular fibers that arise on the anterior end and spiral in a counterclockwise direction toward the posterior end of the body (ISHIDA et al 1988).…”
mentioning
confidence: 99%